2019
DOI: 10.1039/c8nr09188a
|View full text |Cite
|
Sign up to set email alerts
|

Maximization of thermal conductance at interfaces via exponentially mass-graded interlayers

Abstract: We propose a strategy to potentially best enhance interfacial thermal transport through solid–solid interfaces by adding nano-engineered, exponentially mass-graded intermediate layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
2

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 41 publications
3
35
2
Order By: Relevance
“…While for the impedance increasing material, when reflected from the second boundary, both the first two waves will exhibit half-wave loss. Therefore, in the long-wave limit, the phonon wave will travel half wavelength closer than the one reflected from the first boundary, leading to destructive interference, and finally promote the thermal transport across the interface which is certainly coincident with simulations [39][40][41]. Since the wavelength is frequency dependent, in other frequency domains, more factors must be considered, such as the thickness of the interfacial medium, so that the constructive or destructive interference between the two waves reflected to the left region occurs.…”
Section: Discussionsupporting
confidence: 63%
“…While for the impedance increasing material, when reflected from the second boundary, both the first two waves will exhibit half-wave loss. Therefore, in the long-wave limit, the phonon wave will travel half wavelength closer than the one reflected from the first boundary, leading to destructive interference, and finally promote the thermal transport across the interface which is certainly coincident with simulations [39][40][41]. Since the wavelength is frequency dependent, in other frequency domains, more factors must be considered, such as the thickness of the interfacial medium, so that the constructive or destructive interference between the two waves reflected to the left region occurs.…”
Section: Discussionsupporting
confidence: 63%
“…However, a further increase in the thickness of the interfacial Si x Ge 1− x alloy region resulted in lower h K due to the dominant effect of alloy scattering intrinsic to the finite thickness interfacial region over the enhancement due to the reduction in the lattice and mass mismatch. Moreover, the functional form of the concentration profile of the intermixing region at the interface has also been shown to alter interfacial conductance …”
Section: Effect Of Nanostructuring and Surface Functionalizationmentioning
confidence: 99%
“…Another approach to enhance h K across interfaces is by altering the vibrational density of states at the interfacial region through engineering mass graded boundaries via intermixing of the species or by insertion of an interfacial film that bridges the vibrational properties of the two solids in contact. [65,90,103,137,[153][154][155] In comparison to a sharp and abrupt interface, the compositionally disordered (and mass graded) interfaces can demonstrate enhanced h K through vibrational impedance matching between the two solids along with opening new channels of heat transport via anharmonic interactions. For example, Hahn et al [156] have shown that an alloy of Si x Ge 1−x at the Si/Ge interface with a finite thickness of ≈0.5 nm can increase h K by ≈24%.…”
Section: Effect Of Nanostructuring and Surface Functionalizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the bridging layer, in the non-additive harmonic regime, decreases available modes and limits the possibility of enhancing conductance, G, for many combinations of materials. [13,14,17] The transition from the non-additive to the additive regimes depends on anharmonic phonon-phonon scattering processes, and thus on the length of the intermediate layer, L, on the strength of anharmonicity V 0 (the third order of the interatomic force constants) , and on the temperature, T. A comprehensive study on how phonons flow across bridged interfaces in different transport regimes, accessible by varying these parameters, is still missing. Such a study could clarify how different scattering processes determine the transition between additive and non-additive regimes and thus enable better thermal engineering of devices.…”
Section: Introductionmentioning
confidence: 99%